2018
DOI: 10.1590/1678-4499.2017332
|View full text |Cite
|
Sign up to set email alerts
|

Bud load management on table grape yield and quality – cv. Sugrathirteen (Midnight Beauty®)

Abstract: respectively, distributed in 4 plots, considering five plants per replicate. Our results show that pruning seasons significantly affected sprouting percentage. However, the difference in bud load influenced this variable, with higher values in the pruning at 14 buds in both seasons. According to the results, the selection of pruning system according to bud load and to genetic features of the cultivar, and their interaction with the environment, produced higher yields in pruning with 10 buds, without negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…In particular, our trial was carried out in 2018 to 2019 whereas, for Sardinia, the trials were carried out from 2005 to 2007 and the climatic conditions of the seasons could have affected the results since climatic variations have a strong effect on yield and the quality of table grape varieties [36]. With regards to the viticultural practices, the pruning intensity, from 6 to 14 buds left, can influence the potential fertile buds, as reported for Midnight Beauty ® in Brazil, where higher fertile buds were observed in the treatment with a bud load of 8-10 buds per cane [37]. A recent bud dissection study [32] with very long canes (30-nodes) of the Fiesta and Selma Pete varieties showed that nodes in the middle of the cane were the most fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our trial was carried out in 2018 to 2019 whereas, for Sardinia, the trials were carried out from 2005 to 2007 and the climatic conditions of the seasons could have affected the results since climatic variations have a strong effect on yield and the quality of table grape varieties [36]. With regards to the viticultural practices, the pruning intensity, from 6 to 14 buds left, can influence the potential fertile buds, as reported for Midnight Beauty ® in Brazil, where higher fertile buds were observed in the treatment with a bud load of 8-10 buds per cane [37]. A recent bud dissection study [32] with very long canes (30-nodes) of the Fiesta and Selma Pete varieties showed that nodes in the middle of the cane were the most fruitful.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the genotype, long cane pruning may result too in poor shoot renewal lowering yield next season. On the contrary, combined pruning allows usually sufficient and stable yield and at the same time good shoot renewal [21]. A fundamental difference between pitaya and table grape and kiwi vines is that these latter are deciduous, while pitaya maintains reserves in the evergreen cladodes.…”
Section: Discussionmentioning
confidence: 99%
“…Today, for the cultivation of high-quality grafting material of grapes, it is generally accepted to use short pruning and to regulate the load of the vines with buds and shoots, which allows using the growth of the bushes to the maximum for harvesting grape stalks (Ursu, 1989). When determining the load of vines with shoots, their growth strength, soil and climatic conditions and the level of agrotechnics of plantings are considered (Perstnev, 2001;Feitosa et al, 2018;Almanza-Merchán et al, 2014). Other authors believe that the load of vines with shoots should be determined by the amount of annual growth of vines for the previous year or by the amount of phytomass of growth of one-year shoots per vine (Chulkov, Mukhortova, 2018;Kumar et al, 2017).…”
Section: Analysis Of Recent Studies and Publicationsmentioning
confidence: 99%